The Relationship of Perceived Severity and Recurrent Stroke Prevention Behavior at Post-Non-Hemorrhagic Stroke Patients - Rahmawati, Renny Nafia; Lahdji, Aisyah; Anggraini, Merry Tiyas (South East Asia Nursing Research, 2024)
The lack of individual beliefs about the first stroke can cause an increased risk of recurrent stroke in the future causing individuals to behave less well. The theory that can identify individual beliefs for healthy living behavior is the Health Belief Model (HBM), one of which is perceived severity which is the perception of the seriousness of the severity of an illness. This study aimed to determine the relationship between perceived severity and behavior to prevent recurrent stroke in patients after non-hemorrhagic stroke. The study was quantitative descriptive-analytical research with a cross-sectional approach. The research subjects were 70 non-hemorrhagic post-stroke patients at KRMT Wongsonegoro Hospital, Semarang City, using consecutive sampling techniques. Relationship analysis uses the Spearman rank test. Most respondents had sufficient perceived severity as many as 39 respondents (55.7%) and implemented sufficient recurrent stroke prevention behavior in as many as 42 respondents (60%). The Spearman rank test analysis shows that there is a relationship between perceived severity with Recurrent stroke prevention behavior in non-hemorrhagic post-stroke patients (p=0.000) and (r=0.916). Perceived severity is significantly related to adjusting Recurrent stroke prevention behavior in non-hemorrhagic post-stroke patients.